Zakat and Agricultural Productivity in Babura, Nigeria: Empowering Small-Scale Farmers to Achieve the 2nd SDG - Nazifi Dahiru Abdullahi; Ain-Obe Shamsuddin Bolatito (International Journal of Zakat, 2025)
The purpose of this study is to explore how Zakat funds can be leveraged to empower small-scale farmers to facilitate enhanced agricultural outputs and contribute to the 2nd United Nations Sustainable Development Goals (SDGs) of eradicating hunger in Babura Local Government Area of Jigawa State, Nigeria. It is an undeniable fact that Zakat funds are meant for the eight prescribed recipients as enshrined by the Quran, this study through a painstaking and contextual consideration drawing from the opinions of Muslim Jurists seeks to elucidate how this form of almsgiving can mobilize financial resources essential for agricultural improvements in the context of Babura small-scale farmers. This exploration aims to provide a comprehensive framework for understanding the multifaceted role of Zakat in transforming agricultural practices within Babura Town. Qualitative secondary data were sourced from Islamic classical literature, academic journals, books and reports from reputable organizations. The data were evaluated to ensure relevance, credibility and reliability and also validated using data triangulation and comparing findings of other studies. The data were analyzed thematically. The research shows that zakat can significantly improve agricultural productivity among small-scale farmers in Babura Town and contribute to the realization of 2nd SDG. It is recommended that Babura LGA Authorities should partner with local zakat committees to integrate zakat funds into local agricultural policies which can improve access to essential agricultural resources, ensure efficient funds distribution, and train the farmers on sustainable agricultural practices.